Molecular marker assisted back cross breeding for effective transfer of Lr19 in wheat (Triticum aestivum L.) - Pal, Dharam; Bhardwaj, S.C.; Sharma, Pratima; Sharma, Deepak; Kumari, Shilpi; Patial, Madhu; Prabhu, K.V.; Kumar, J. (The Indian Journal of Genetics and Plant Breeding, 2016)
The gene Lr19, derived from Agropyron elongatum provides effective resistance against leaf rust in Northern India.To develop improved wheat lines in the background of HS240, HS295, rust resistance from FLW20 possessing Lr19 was involved to generate back cross populations and confirm resistance through host-pathogen interaction and molecular marker. The SCAR marker SCS265512was used to validate Lr19 in back cross plants transferred from FLW20. Results of HPI test and molecular marker assisted validation for Lr19 showed 88-93 percent consistency, indicating that both the techniques are mutual exclusive for effective selection of Lr19. Fixed gene populations are now ready for station trials.